Burnt out? No, it’s not about me - Gut, Grzegorz; Wąsik, Michał; Śladowski, Dariusz; Olender, Ewa (Family Medicine & Primary Care Review, 2025)
Professional burnout can affect any of us. We enter adulthood with a sense of mission, ready to make sacrifices at any cost, only to collide painfully with reality. We experience severe physical fatigue, frustration, disappointment, discouragement, somatic problems, and addictions. We suffer like everyone else but pretend that everything is fine, refusing help. Over time, we become too unwell to care for ourselves. As it turns out, there are people and organizations ready to help – if we only allow ourselves to accept it.